Dehydroepiandrosterone: a potential therapeutic agent in the treatment and rehabilitation of the traumatically injured patient. Issue 1 (2nd August 2019) - Bentley, Conor; Hazeldine, Jon; Greig, Carolyn; Lord, Janet; Foster, Mark
Abstract: Severe injuries are the major cause of death in those aged under 40, mainly due to road traffic collisions. Endocrine, metabolic and immune pathways respond to limit the tissue damage sustained and initiate wound healing, repair and regeneration mechanisms. However, depending on age and sex, the response to injury and patient prognosis differ significantly. Glucocorticoids are catabolic and immunosuppressive and are produced as part of the stress response to injury leading to an intra-adrenal shift in steroid biosynthesis at the expense of the anabolic and immune enhancing steroid hormone dehydroepiandrosterone (DHEA) and its sulphated metabolite dehydroepiandrosterone sulphate (DHEAS). The balance of these steroids after injury appears to influence outcomes in injured humans, with high cortisol: DHEAS ratio associated with increased morbidity and mortality. Animal models of trauma, sepsis, wound healing, neuroprotection and burns have all shown a reduction in pro-inflammatory cytokines, improved survival and increased resistance to pathological challenges with DHEA supplementation. Human supplementation studies, which have focused on post-menopausal females, older adults, or adrenal insufficiency have shown that restoring the cortisol: DHEAS ratio improves wound healing, mood, bone remodelling and psychological well-being. Currently, there are no DHEA or DHEAS supplementation studies in trauma patients, but we review here the evidence for this potential therapeutic agent in the treatment and rehabilitation of the severely injured patient.